Coordinated Management of COVID-19 Response: Lessons From Whole-of-Society and Whole-of-Health Strategies in Wuhan, China - Chen, Shanquan; Zhang, Pan; Zhang, Yun; Fung, Hong; Han, Yong; Law, Chi Kin; Li, Zhiqiang (Frontiers in Public Health, 2021)
Background: The outbreak of novel coronavirus disease 2019 (COVID-19) has been challenging globally following the scarcity of medical resources in light of the surge in demand. As the pandemic continues, the question remains on how to accomplish more with existing resources and improve the efficiency of existing health care delivery system worldwide. In this study, we reviewed the experience from Wuhan - the first city to experience COVID-19 outbreak – that has presently shown evidence for efficient and effective control of the epidemic locally. Material and Methods: We performed a retrospective qualitative study based on the document analysis of COVID-19-related materials and interview with first-line people in Wuhan. Results: We extracted two themes (including the evolution of Wuhan’s prevention and control strategies on COVID-19 and corresponding effectiveness) and four sub-themes (including routine prevention and control period, exploration period of targeted prevention and control strategies, mature period of prevention and control strategies, and recovery period). How Wuhan combatted COVID-19 through multi-tiered and multi-sectoral collaboration, overcoming its fragmented, hospital-centred, and treatment-dominated healthcare system, were illustrated and summarized. Conclusion: Four lessons for COVID-19 prevention and control were summarised: (a) Engage the communities and primary care not only in supporting but also in screening and controlling, and retain it as among the first line of COVID-19 defence; (b) Extend and stratify the existing health care delivery system; (c) Integrate person-centred integrated care into the whole coordination; and (d) Delink the revenue relationship between doctors and patients and safeguard free-will of physicians when treating patients.